Role of cone beam computed tomography in the prompt diagnosis of a nasopalatine duct cyst - Sapna Panjwani (Journal of Indian Academy of Oral Medicine and Radiology, 2014)
The nasopalatine duct cyst (NPDC) is the most common of all the developmental, epithelial, and non-odontogenic cysts of the maxilla, believed to originate from the epithelial remnants of the nasopalatine duct. Typically, the lesion is asymptomatic and is detected accidentally on a radiograph. The definite diagnosis must be based on the clinical, radiological, and histopathological findings. Frequently misdiagnosed, the NPDC is not rare. The motive of reporting an entity that is not very rare is that the lesion is mostly misdiagnosed, and to emphasize the importance of cone-beam computed tomography (CBCT) in the diagnosis and optimized treatment planning of NPDCs.